The benefit of delithiated beta spodumene to reduce the carbon footprint of cemented paste backfill - Safari, A; Lim, H (Paste 2023: 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
Delithiated beta spodumene (DBS) is the leach residue produced after lithium refining. It represents the largest material stream produced in the process; approximately seven to ten tonnes of DBS is generated per tonne of lithium hydroxide monohydrate produced. The material is characterised as pozzolanic and is featured in the recently published standard AS3582.4:2022 Supplementary cementitious material: Manufactured Pozzolans. This paper presents an experimental study on the strength behaviour of cemented paste backfill (CPB) containing DBS by investigating different CPB mix designs produced with nickel tailings, mine site-specific recycled process water, and various types of binders. The primary motivation of this collaborative research work was to find ways to reduce CPB’s carbon footprint by using locally sourced material as a binder additive. For this study, several laboratory tests were undertaken at the Nova nickel-copper mine to explore the use of DBS in paste fill design. DBS was used as a partial replacement material for ground granulated blast-furnace Slag (GGBFS) in 9:1 slag-lime binder and mixes with other cementitious binder types such as general purpose (GP), general blended (GB), high early strength (HE), and low heat (LH) cement. The results demonstrated that CPB samples with the DBS-GB, DBS-GP, DBS-HE and DBS-LH mixed binders showed promising results with DBS replacement ratios of up to 40 wt.%; however, CPB samples with the DBS- lime mixes failed to perform to an acceptable strength. Nevertheless, these performed well in achieving the compressive strength required for use at the Nova mine site. At 40 wt.% binder replacement with DBS, paste CO2 emission will be reduced by around 28%. Future studies may consider the long-term performance and other mining applications of DBS.
Keywords: cemented paste backfill (CPB); recycling; delithiated beta spodumene (DBS); cementitious material; lithium leach residue